The Real Challenge of Climate Change - Brooks, Thom (PS: Political Science and Politics, 2013)
Climate change is confirmed by a global scientific consensus. Although no serious disagreement about whether climate change exists, deep controversy remains about what should be done about its many harmful effects. These effects are wide-ranging and include, for example, the increasing threat to coastal wetlands from rising sea levels, the greater likelihood of droughts harming agricultural production, and the spread of tropical diseases (Pachauri and Reisinger 2008). One further effect is the increasing risk of triggering an environmental catastrophe, such as an ice age, that might result in major loss of human lives. Thom Brooks is reader in law at Durham Law School. He was previously reader in political and legal philosophy at Newcastle University, and Brooks held visiting appointments at Oxford, St Andrews, and Uppsala. He holds a visiting scholarship at St John's College, Oxford. Brooks is an academician in the Academy of Social Science and a fellow of the Royal Historical Society and the Royal Society of Arts. Brooks works broadly in the areas of ethics, law, and public policy. Current research interests include criminal justice, citizenship and immigration, global justice, and public policy reform. Brooks is the author of two recent books including Hegel's Political Philosophy (2007, 2012) and Punishment (2012). He has edited several books and a five-volume collection on papers in criminal law and philosophy (forthcoming). His current book project is Rawls' Political Liberalism coedited with Martha C. Nussbaum. His research on criminal justice has featured in the RCUK Report on the top 100 Big Ideas for the Future. He can be reached at thom.brooks@durham.ac.uk
EPrint Processing Status: Full text deposited in DRO